Single Ethanol Withdrawal Regulates Extrasynaptic δ-GABAA Receptors Via PKCδ Activation - Chen, Juan; He, Yang; Wu, Yan; Zhou, Hang; Su, Li-Da; Li, Wei-Nan; Olsen, Richard W.; Liang, Jing; Zhou, Yu-Dong; Shen, Yi (Frontiers in Molecular Neuroscience, 2018)
Alcohol (ethanol, EtOH) is one of the most widely abused drugs with profound effects on brain function and behavior. GABAA receptors (GABAARs) are one of the major targets for EtOH in the brain. Temporary plastic changes in GABAARs after withdrawal from a single EtOH exposure occur both in vivo and in vitro, which may be the basis for chronic EtOH addiction, tolerance and withdrawal symptoms. Extrasynaptic δ-GABAAR endocytosis is implicated in EtOH-induced GABAAR plasticity, but the mechanisms by which the relative abundance and localization of specific GABAARs are altered by EtOH exposure and withdrawal remain unclear. In this study, we investigated the mechanisms underlying rapid regulation of extrasynaptic δ-GABAAR by a single EtOH withdrawal in cultured rat hippocampal neurons. Thirty-min EtOH (60 mM) exposure increased extrasynaptic tonic current (Itonic) amplitude without affecting synaptic GABAAR function in neurons. In contrast, at 30 min after withdrawal, Itonic amplitude and responsiveness to acute EtOH were both reduced. Similar results occurred in neurons with okadaic acid (OA) or phorbol 12,13-dibutyrate (PDBu) exposure. PKC inhibition prevented the reduction of Itonic amplitude and the tolerance to acute EtOH, as well as the reduction of GABAAR-δ subunit abundance induced by a single EtOH withdrawal. Moreover, EtOH withdrawal selectively increased PKCδ level, whereas PKCδ inhibition specifically rescued the EtOH-induced alterations in GABAAR-δ subunit level and δ-GABAAR function. Together, we provided strong evidence for the important roles of PKCδ in the rapid regulation of extrasynaptic δ-GABAAR induced by a single EtOH withdrawal.